An Omni‐Healable and Highly Sensitive Capacitive Pressure Sensor with Microarray Structure. Issue 63 (17th October 2018) - Liu, Feng; Han, Fei; Ling, Lei; Li, Jinhui; Zhao, Songfang; Zhao, Tao; Liang, Xianwen; Zhu, Deliang; Zhang, Guoping; Sun, Rong; Ho, Derek; Wong, Ching‐Ping
Abstract: Capacitive pressure sensors with high flexibility, sensitivity, and excellent healable properties are desirable for a wide variety of applications, such as e‐skin. However, implementing these characteristics onto a device presently remains a great challenge. In this work, a flexible pressure sensor with high sensitivity and strong healable properties has been developed based on healable polyurethane (HPU), silver nanowires and graphene. The HPU‐based microstructured capacitive pressure sensor exhibited a high sensitivity of 1.9 kPa −1 (<3 kPa), a fast response time (<100 ms), low detection limit (10 Pa), and long‐term durability (1000 cycles). Touch‐finger and vocal‐cord vibration detection have been demonstrated and exhibit a high sensitivity to both static and dynamic pressure. More notably, the entire pressure sensor including the dielectric layer and electrodes is omni‐healable after complete separation. The prototype has experimentally shown tremendous potential for wearable, healable applications, such as healthcare monitoring and human‐machine interfaces. Abstract : A flexible pressure sensor with both high sensitivity and the capability of omni‐healability has been developed based on healable polyurethane (HPU), silver nanowires (AgNWs), and graphene. The HPU‐based sensor can reach a sensitivity of 1.9 kPa −1 (<3 kPa), has a fast response time (<100 ms), low detection limit (10 Pa), and long‐term durability (1000 cycles; see figure). More importantly, the pressure sensor including electrodes and dielectric, can realize omni‐healable after mechanical damage.